THE EFFECT OF PICTURE CARD ON ISLAMIC JUNIOR HIGH SCHOOL STUDENTS’ VOCABULARY LEARNING - Sang Diah Putri Maulana (Graduate Program, University of Islam Malang, 2021)
It is said that one of language sources is sources. The point of this research is to see the understudies' capacity in dominating English vocabulary utilizing picture cards. This examination utilized quasi-experimental. The understudies who are sitting in the experimental class was encouraged utilizing picture cards while the individuals who was sitting in the control class was educated traditionally. The example was 40 understudies who were placed in those two classes (20 understudies were in experimental class and the other 20 understudies were in the controlled class). This examination followed three stages: pre-test, treatment, and post-test. The information were gathered through the test and the gathered information were broke down utilizing t-test equation with the assistance of SPSS. The discoveries of the examination indicated that the mean scores of the experimental group and the controlled group were unique. In light of the information examination, the critical section estimation of t-test was 0.003 < 0.05, it showed that the consequence of t-test investigation was huge or significant. In addition, the findings simply lead to making students more excited and involved in the learning process. This also provided evidence for this study using the Picture Card technique, so that the teacher could select the right technique to achieve the goal of teaching vocabulary, in particular, in the teaching of vocabulary. The result of this study showed that picture cards could give good effects on the students’ vocabulary learning. Then, the researcher concluded that the picture cards could be used as an alternative teaching medium to push the students' vocabulary learning in the seventh grade of junior high school. Key Words : Picture Card, Vocabulary